Z-100, extracted from Mycobacterium tuberculosis strain Aoyama B, promotes TNF-α production via nucleotide-binding oligomerization domain containing 2 (Nod2)-dependent NF-κB activation in RAW264.7 cells. Issue 1 (March 2015) - Katsunuma, Kokichi; Yoshinaga, Koji; Ohira, Yuta; Eta, Runa; Sato, Takanori; Horii, Takayuki; Tanaka, Takao; Takei, Mineo; Seto, Koichi
Highlights TNF-α production from RAW264.7 cells was induced by Z-100 and IFN-γ stimulation. Nod2 expression was up-regulated by IFN-γ treatment in RAW264.7 cells. Z-100-induced TNF-α production was attenuated by Nod2 gene silencing. Z-100 activates Nod2-dependent NF-κB signaling.